Concomitant Use of Topiramate Inducing Neutropenia in a Schizophrenic Male Stabilized on Clozapine. (24th January 2016) - Sharma, Pravesh; Davis, Jeffrey; Rachamallu, Vivekananda; Aligeti, Manish
Abstract : This is a case of a 23-year-old African American male with a history of paranoid schizophrenia that developed neutropenia on a clozapine-topiramate therapy. Clozapine had well addressed the patient's psychotic symptoms, while topiramate was used as a weight-lowering agent. The patient had fairly stable leukocyte counts for eight months on clozapine 300 mg and topiramate 100 mg daily. Doubling the dosage of topiramate led to severe neutropenia after two months. Reviewing the patient's laboratory reports showed a gradual decline of neutrophils occurring at a lower dosage, followed by a rapid decline after an increased dosage. In this case, we report that not only did topiramate act as the neutropenic agent, but also it might have done so in a dose-dependent manner.